Environmental DNA adsorption to chitin can promote horizontal gene transfer by natural transformation - Jacob D. Holt; Yixuan Peng; Triana N. Dalia; Ankur B. Dalia; Carey D. Nadell (Proceedings of the National Academy of Sciences, 2025)
Horizontal gene transfer by natural transformation (NT) is induced in Vibrio cholerae upon attachment to chitin surfaces in the aquatic environment. Here, we show that free environmental DNA adsorbs to chitin surfaces under physiologically realistic conditions. Using live-cell imaging and a fluorescent NT reporter, we demonstrate with cellular resolution microscopy that V. cholerae utilizes chitin-bound DNA as a reservoir for genetic exchange. Additionally, we demonstrate that uptake of DNA from this chitin-bound reservoir requires the forceful retraction of competence type IV pili. These findings uncover a role for retraction force in driving pilus-dependent NT and suggest that chitin particle surfaces can act as hotspots for horizontal gene transfer.